2001
DOI: 10.1016/s0168-6445(01)00056-0
|View full text |Cite
|
Sign up to set email alerts
|

The virulence factors of Bordetella pertussis: a matter of control

Abstract: Bordetella pertussis is the causative agent of whooping cough, a contagious childhood respiratory disease. Increasing public concern over the safety of whole-cell vaccines led to decreased immunisation rates and a subsequent increase in the incidence of the disease. Research into the development of safer, more efficacious, less reactogenic vaccine preparations was concentrated on the production and purification of detoxified B. pertussis virulence factors. These virulence factors include adhesins such as filam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
51
0
9

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 198 publications
(319 reference statements)
0
51
0
9
Order By: Relevance
“…The majority of virulence factors in the bordetellae are regulated by the two-component system BvgAS (34,52). In response to environmental stimuli, the BvgAS system regulates the transcription of several target genes (13).…”
mentioning
confidence: 99%
“…The majority of virulence factors in the bordetellae are regulated by the two-component system BvgAS (34,52). In response to environmental stimuli, the BvgAS system regulates the transcription of several target genes (13).…”
mentioning
confidence: 99%
“…B. pertussis produces many virulence factors that are responsible for the clinical features of the disease (9,20,26). The virulence factors of B. pertussis are generally divided into two groups, adhesins and toxins.…”
mentioning
confidence: 99%
“…Twenty-five years ago, Ofek et al showed that surface-exposed bacterial lectins were required for initiation of infection (44). Since then, several bacterial lectins have been shown to be involved in the attachment of host cell glycoconjugates, such as the P pili and type 1 fimbriae of Escherichia coli (78), the filamentous hemagglutinin of Bordetella pertussis (63), several adhesins of nontypeable Haemophilus influenzae (70), and type IV pili of Pseudomonas aeruginosa (20).…”
mentioning
confidence: 99%